POPULASI DAN SERANGAN LIRIOMYZA SATIVAE (BLANCHARD) (DIPTERA: AGROMYZIDAE), SERTA POTENSI PARASITOIDNYA PADA PERTANAMAN KETIMUN - Siti Herlinda, Leny Puspa Rosalina, Yulia Pujiastuti, Erizal Sodikin, dan Aunu Rauf (Universitas Lampung, 2005)
Population and damage by Liriomyza sativa (Blanchard) (Diptera : Agromyzidae) and its parasitoid potential on cucumber fields. The objectives of this research were to figure out adult population of L. sativae and the damage caused by the larvae on cucumber leaves, to analyze the relationship between adult population and the number of leaf mining tunnel caused by L. sativae larvae, and to analyze the relationship betweeen the larval abundance and its parasitoids. The highest adult population (7.60 adults per trap) of L. sativae was found on 5 weeks after planting (WAP) and the lowest (3.20 adults per trap) was on 2 WAP. The highest damage intensity was found on 3 weeks after planting, amounted to 36.89% while the lowest was found on 6 weeks after planting, amounted to 12.12%. The regression coefficient showed that each adult of L. sativae caused one leaf mining tunnel. The higher the number of L. sativae larvae, the more the mining tunnels occured (R = 80.8%). The higher the number of L. sativae larvae in cucumber leaves, the more the larvae parasitized (R = 86.8%). Parasitoids found were Diglyphus sp. (Hymenoptera : Eulophidae) and Neochrysocharis sp. (Hymenoptera : Eulophidae). The highest apparent parasitism was found on 5 weeks after planting, amounted to 41.9%.